Effect of Metallographic Sample Preparation Processes on Retained Austenite Volume Fraction in Quenched AISI 52100 Steel - Burak NALÇACI; Volkan KILIÇLI; Mehmet ERDOĞAN (Gazi Üniversitesi Fen Bilimleri Dergisi, 2020)
Sample preparation is one of the main steps in metallographic examinations and the sample preparation processes give rise to changes in the determination of volume fraction of any phases can cause failure at the interpretation of a study. In this study, the effect of applied load during the metallographic sample preparation process on the volume fraction of retained austenite of the quenched AISI 52100 was investigated. Metallographic examination samples were prepared under different loads (20N, 40N, 80N, 100N) were examined by optical and SEM microscopes. The retained austenite volume fraction was calculated by the direct comparison method from the XRD analysis. Surface roughness was determined via a profilometer in order to reveal the effect of surface roughness on XRD patterns. Hardness measurements were performed to determine the probability of applied load that may transform retained austenite into martensite and rise in macro hardness after this transformation. No significant phase transformation was observed in the retained austenite phase volume fraction of metallographic examination samples prepared under different loads on retained austenite volume fraction measurements by the XRD method and. It is thought that a large amount of martensite volume fraction applies compressive stress on the retained austenite owing to low retained austenite volume fraction (<%10) is the reason for not being observed phase transformation.